The Effects of Addition Recombinant Growth Hormones with Different Doses on the Growth and Survival of White Shrimp (Penaeus merguiensis) - Manurung, Fazhira Ryunisyah; Rusliadi, Rusliadi; Nur, Abidin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThe research was conducted in Juli 2019 – Agustus 2019 at BBPBAP Jepara, the aim to determine the effect and get the best dose of recombinant growth hormone grouper fish (rElGH) for growth and survival of white shrimp (Penaeus merguiensis). This research was conducted using experimental methods with completely randomized design (CRD) with one factor, five levels of treatment and three replications. The treatment was used sink dose of 0 mg/L, 10 mg / L, 15 mg / L, 20 mg / L, 25 mg / L. White shrimp used was PL10 stadia with an average weight of 0.0017 g. The results showed that the added of rElGH by immersion method significantly affected (P <0.05) the growth of absolute weight, specific growth rate of PL10 white shrimp stage. Addition of recombinant growth hormone at dose of 20 mg / L gave the best results on growth of absolute weight 0.1642 g and specific growth rate of 13.47% and survival rate of 93.3%. Keywords : recombinant rElGH growth hormone, white shrimp, growth.